1976
DOI: 10.1080/17450397609423258
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Wirkung von Proteinaseinhibitoren bei Ratten

Abstract: Short-term trials with a triazin derivative and a peptide aldehyde were carried out to investigate the in-vivo administration of proteinase inhibitors in rats for improving the N balance of the animals. The results of N balances suggest that the peptide aldehyde may be regarded as a promising substance that may be used to increase the rate of utilization of the absorbed N in the intermediary metabolism. The short-term use of both active compounds did not affect the true N digestibility. The two compounds did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In earlier experiments with rats we found values for the half-life for protein breakdown in the small and large intestine of 1.6 and 2.6 d respectively (Simon, Bohley, Huckel, Munchmeyer & Bergner, 1976).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In earlier experiments with rats we found values for the half-life for protein breakdown in the small and large intestine of 1.6 and 2.6 d respectively (Simon, Bohley, Huckel, Munchmeyer & Bergner, 1976).…”
Section: Discussionmentioning
confidence: 86%
“…Some investigators suggest that amino acids from an extracellular precursor pool may move directly into the synthetic machinery (Kipnis, Reiss & Helmreich, 1961;London, I 972;Venrocij, Poort, Kramer & Jansen, 1972). However, other investigators have concluded that the intracellular pool or some portion of it, represents the true source of amino acids (Tsukada, Moriyama & Lieberman, 1971 ;Alpers & Thier, 1972;Fern & Garlick, 1973Li, Fulks & Goldberg, 1973). Airhart et af.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leupeptin, an inhibitor of both serine and cysteine proteinases, inhibits basal protein turnover by 30-40 % (Dean, 1979). Initial experiments looking at the inhibitory characteristics of this compound seemed to indicate that it rapidly entered cells by diffusion, since its effect was observed without any discernible lag time (Simon et al, 1977;Seglen et al, 1979). In conflict with these results, Nonaka and colleagues (1982) administered [14C]leupeptin orally to dystrophic chickens and looked at the distribution of [14C]leupeptin.…”
Section: Introductionmentioning
confidence: 99%